Not Just Listening to the Teacher's Voice: A Case Study of a University English Teacher's Use of Audio Feedback on Social Media in China - Xu, Yueting (Frontiers in Education, 2018)
A teacher’s feedback is one of the most important aspects of student learning. Although feedback can arguably move students from their current level to their desired goals, students in higher education rate it as one of the least satisfactory areas partly because of the unidirectional nature of written feedback. This paper contains a case study of a university English teacher’s use of audio feedback on a popular social media platform in China. This study includes an analysis of the teacher’s audio feedback and follow-up interactions with students on the popular WeChat application, teacher interviews, student reflective journals and 10 classroom observations of student presentations. The study found that many features of the teacher’s audio feedback contributed to student learning. Findings also reveal how the instructor’s audio feedback on social media created opportunities for dialogic feedback by increasing student engagement with the comments and enhancing meaning negotiation, as well as how the teacher and students perceive the use of audio feedback. These findings are discussed in terms of creating dialogical feedback contexts for student learning, incorporating use of audio feedback into teacher assessment literacy, and utilizing social media as an innovative platform for audio feedback. It concludes with implications for feedback practice in higher education and teacher assessment education.